Macroscopic superconducting phenomena : an interactive guide - Badía-Majós, Antonio (IOP (Series). Release 21., 2021)
A number of macroscopic manifestations of superconducting phenomena (such as zero electrical resistance, the expulsion of magnetic fields and the Josephson effect) have resulted in a proliferation of applications in engineering and electronics. This book takes a practical, pedagogical approach to understanding the electromagnetic properties of superconducting materials. The reader is provided with a set of ready-to-use interactive tools to engage with topics such as vanishing resistivity, magnetic flux expulsion, flux pinning, critical currents, flux quantization and more. Aimed at high level undergraduate and graduate physicists and engineers, this book is ideal for early researchers studying macroscopic superconductivity.